Дискретне Фур’є-продовження як алгоритм прогнозування фінансово-економічних часових рядів - Chabanenko, D. M. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2012)
The time series forecasting method, based on determination of the frequencies spectrum, is offered. The method is based on time series approximation in the interval training of analytic function, that contains the trend and harmonic oscillations combination. The effectiveness of the proposed method for the financial-economical time series forecasting is showed with the help of experimental approbation.